ZAKAT PRODUKTIF DALAM PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH (UMKM) DAN DAMPAKNYA TERHADAP PENINGKATAN KESEJAHTERAAN MUSTAHIK : MODEL CIBEST DI BAZNAS KABUPATEN CIREBON - Nurjanah Norfairuz (UIN Siber Syekh Nurjati Cirebon, 2020)
This study intends to examine changes in household income Mustahik before and after receiving productive zakat funds based on the CIBEST Model. The results showed that based on the CIBEST model the material poverty index decreased by 0.24 or 24 percent out of material poor conditions after the provision of productive zakat and guidance. Furthermore the spiritual poor index from 0.12 or 12 percent fell to 0 percent after the existence of productive zakat funds and guidance. Likewise, absolute poverty from 0.1 or 1 percent to 0 percent of households must come out of absolute poverty. And the welfare index has increased by 46 percent of zakat after zakat assistance and guidance and managed to enter into the welfare category.